Hunting territories and land use overlap in sedentarised Baka Pygmy communities in southeastern Cameroon - Fa, J.E.; Brull, G.R.; Martín, E.Á.; Okale, R.; Fouda, F.; Farfán, M.A.; Cain, B.; Fisher, R.; Coad, L.M.; Funk, S.M. (Springer, 2021)
A significant number of Baka Pygmies in Cameroon have been sedentarised in roadside villages, in contrast to their nomadic hunter-gatherer existence of the past. Although this change in lifestyle has had important consequences on health, most Baka villages still supplement their diets from forest products, especially wild meat. We used a combination of participatory methods and monitoring of individual hunters to map hunting territories in 10 Baka villages in southeastern Cameroon. From these, we determined whether wild meat extraction levels per village were related to the size of hunting territories, measured habitat use by hunters and finally defined the overlap between hunting territories and extractive industries in the region. Mapped village hunting areas averaged 205.2 ± 108.7 km2 (range 76.8–352.0 km2); all villages used a total of 2052 km2. From 295 tracks of 51 hunters, we showed that hunters travelled an average of 16.5 ± 13.5 km (range 0.9–89.8 km) from each village. Home ranges, derived from kernel utilization distributions, were correlated with village offtake levels, but hunter offtake and distance travelled were not significantly related, suggesting that enough prey was available even close to the villages. Hunters in all village areas exhibited a clear bias towards certain habitats, as indicated by positive Ivlev’s index of selectivity values. We also showed that all village hunting territories and hunter home ranges fall within mining and logging concessions. Our results are important for local understanding of forest land uses and to reconcile these with the other land uses in the region to better inform decisions concerning land use policy and planning.